Differential regulation of jasmonate responses in multiple jaz mutants. (31st December 2022) - Zhang, Yue; Liu, Bei; Zhai, Jiaqi; Wang, Qinglei; Song, Susheng
ABSTRACT: The phytohormones jasmonates (JAs) regulate diverse aspects of plant growth and defense responses. The JA-ZIM domain (JAZ) family of repressors are targeted by the JA receptor Coronatine Insensitive 1 for ubiquitination and subsequent degradation via the 26S proteasome. We previously investigated the functions of JAZs in JA responses by analyzing jaz mutants of the phylogenetic group I ( jaz1/2/5/6 ), group II/III ( jaz10/11/12 ), group IV/V ( jaz3/4/7/9 and jaz3/4/7/8/9 ), and their high-order mutant jaz1/2/3/4/5/6/7/9/10/11/12 . Here, we examined JA-regulated root growth, apical hook curvature, flowering time, and defense against the insect Spodoptera exigua in the intermediate jaz mutants jaz1/2/5/6/10/11/12, jaz1/2/3/4/5/6/7/9, and jaz3/4/7/8/9/10/11/12 . This study shows that these jaz mutants differentially affect JA responses, suggesting the complexity of JA pathway in these multiple jaz mutants.